2019
DOI: 10.1039/c9cc02186h
|View full text |Cite
|
Sign up to set email alerts
|

Parahydrogen induced hyperpolarization provides a tool for NMR metabolomics at nanomolar concentrations

Abstract: Sensitivity enhancement by parahydrogen hyperpolarization allows NMR detection and quantification of hundreds of urinary metabolites at down to nanomolar concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(128 citation statements)
references
References 33 publications
3
125
0
Order By: Relevance
“…1) are not chemically equivalent, which, due to the distribution of p-H 2 association in time, causes rapid conversion of the singlet state to longitudinal spin order (Buljubasich et al, 2013). We have previously demonstrated that this spin order can be converted into enhanced magnetization, allowing the NMR detection of hydride signals down to sub-micromolar complex concentrations (Eshuis et al, 2015;Sellies et al, 2019). This sensitivity increase can also be used to study the exchange of p-H 2 in the iridium catalyst as well as the NMR relaxation of the hydrides and p-H 2 in solution.…”
Section: Phip-nmr Pulse Sequences For Hydrogen Kinetics/relaxationmentioning
confidence: 99%
See 4 more Smart Citations
“…1) are not chemically equivalent, which, due to the distribution of p-H 2 association in time, causes rapid conversion of the singlet state to longitudinal spin order (Buljubasich et al, 2013). We have previously demonstrated that this spin order can be converted into enhanced magnetization, allowing the NMR detection of hydride signals down to sub-micromolar complex concentrations (Eshuis et al, 2015;Sellies et al, 2019). This sensitivity increase can also be used to study the exchange of p-H 2 in the iridium catalyst as well as the NMR relaxation of the hydrides and p-H 2 in solution.…”
Section: Phip-nmr Pulse Sequences For Hydrogen Kinetics/relaxationmentioning
confidence: 99%
“…1b). We have previously demonstrated that such an asymmetric complex is an ideal NMR chemosensor (Hermkens et al, 2016;Sellies et al, 2019): molecules capable of associating with the PHIP catalyst can be probed by a pair of hydride signals enhanced by ca. 3 orders of magnitude with respect to thermal NMR measured at 500 MHz.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations